React Application Architecture for Production : Learn Best Practices and Expert Tips to Deliver Enterprise-Ready React Web Apps. - Alickovic, Alan (Packt Publishing, Limited, 2023)
A hands-on guide to help you develop skills and confidence in building and structuring React applications in a well-organized way using the best tools in the React ecosystem Key Features Discover solutions to complex problems faced while creating production-ready apps with React Develop scalable React applications with Next.js using a step-by-step approach from analysis to deployment Get an overview of the React ecosystem and identify the best tools to meet your app requirements Book Description Building large-scale applications in production can be overwhelming with the amount of tooling choices and lack of cohesive resources. To address these challenges, this hands-on guide covers best practices and web application development examples to help you build enterprise-ready applications with React in no time. Throughout the book, you'll work through a real-life practical example that demonstrates all the concepts covered. You'll learn to build modern frontend applications--built from scratch and ready for production. Starting with an overview of the React ecosystem, the book will guide you in identifying the tools available to solve complex development challenges. You'll then advance to building APIs, components, and pages to form a complete frontend app. The book will also share best practices for testing, securing, and packaging your app in a structured way before finally deploying your app with scalability in mind. By the end of the book, you'll be able to efficiently build production-ready applications by following industry practices and expert tips. What you will learn Use a good project structure that scales well with your application Create beautiful UIs with Chakra UI and emotion Configure a base Next.js app with static code analysis and Git hooks Learn to mock API endpoints for prototyping, local development and testing Choose an optimal rendering strategy in Next.js based on the page needs Learn to choose the best state management solution for given problem Write unit tests, integration tests and e2e tests in your React Application Deploy your React applications on Vercel Who this book is for This book is for intermediate-level web developers who already have a solid understanding of JavaScript, React, and web development in general and want to build large-scale React applications effectively. Beginner-level TypeScript experience, along with JavaScript and React, will be beneficial.